COVID-19 impact on high stakes assessment: a New Zealand journey of collaborative adaptation amidst disruption - Poskitt J (Taylor and Francis Group, 2022)
New Zealand’s defined coastal boundaries, isolation and small population were favourable factors to minimise the spread of COVID-19. Decisive governmental leadership and a public willing to comply with high-level lockdown in the first phase, resulted in minimal disruption to assessment. But as the pandemic progressed through Delta and Omicron variants, concerns grew about equitable access to assessments, declining school attendance, and inequitable educational outcomes for students, especially of Māori and Pacific heritage. School and educational agency experiences of high stakes assessment in a period of uncertainty were examined through document analysis and research interviews. Using Gewirtz’s contextual analysis of the multi-dimensional and complex nature of justice, and Rogoff’s conceptual framework of three planes of socio-cultural analysis: the personal (learner), inter-personal (school) and institutional (educational agencies), revealed that though collaborative adaptations minimised assessment disruptions on wellbeing and equity of access, they did not transform high stakes assessment.
Keywords: Assessment; COVID-19; New Zealand; senior secondary school; well-being; 1303 Specialist Studies in Education; 1701 Psychology